Karakteristik Tradisi Rokat Pernikahan Pada Calon Pengantin: Studi Kasus di Desa Muneng Kidul Kecamatan Sumberasih Sumberasih Kabupaten Probolinggo - Rini Nadira Yulianti Rini; Ana Billah Ana (Journal of Innovative and Creativity, 2025)
This study aims to analyze the social, spiritual, and cultural meanings of the rokat marriage tradition in Muneng Kidul Village, Sumberasih District, Probolinggo Regency, as well as its influence on the attitudes and perceptions of prospective brides and grooms. The rokat tradition, a pre-marital ritual typical of the Madurese community in Probolinggo, functions not only as a purification ceremony but also as a mechanism for socializing moral values, strengthening social solidarity, and symbolizing cultural identity. This research employs a qualitative approach with ethnographic methods, including in-depth interviews, participant observation, and documentation. The findings indicate that the rokat tradition plays a vital role in shaping the perspectives of prospective couples regarding the meaning of marriage, social responsibility, and spiritual readiness for family life. Furthermore, the continuity of this tradition is supported by the roles of traditional and religious leaders, the value of mutual cooperation (gotong royong), and the community’s collective consciousness in preserving cultural heritage. Despite modernization, the community has adapted by simplifying certain ritual processes and utilizing digital media for documentation while maintaining its sacred essence. Based on functionalist and phenomenological theories, rokat can be understood as a cultural practice that sustains social cohesion while reinforcing the spiritual experience and cultural identity of the Probolinggo community.